2015
DOI: 10.3109/15622975.2015.1091501
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy and cognitive functions in treatment-resistant depression

Abstract: The negative effects of ECT on the reported measures of cognition are transient. After 3 months, the indices of memory were significantly better than before the treatment. In addition to its antidepressant effect in DRD, ECT may also exert a long-term favourable influence on some cognitive functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
23
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 13 publications
10
23
2
Order By: Relevance
“…Our results are in accordance with the majority of recent studies showing stability of cognitive performance as well as improvements in processing speed with ECT in the short-term (baseline to end of index) and long-term (after 6-months) (22, 25, 47, 49, 50). Semkovska, Bodnar, and Fernie reported significant improvement in cognition at varying time points after ECT completion (2 weeks (22), 3 months (50), and 6 months (25) respectively).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in accordance with the majority of recent studies showing stability of cognitive performance as well as improvements in processing speed with ECT in the short-term (baseline to end of index) and long-term (after 6-months) (22, 25, 47, 49, 50). Semkovska, Bodnar, and Fernie reported significant improvement in cognition at varying time points after ECT completion (2 weeks (22), 3 months (50), and 6 months (25) respectively).…”
Section: Discussionsupporting
confidence: 93%
“…Here, we also show that improvements in processing speed and attention may be at least partly attributable to practice effects. Only acute adverse effects of ECT on verbal memory and executive function (specifically inhibition) after two sessions of ECT were observed; unlike some other studies these effects were not present after the index series was completed or at the 6-month follow-up (22, 50). In the current study, ECT did not have a long-term adverse effect on cognition and actually showed improvements in some aspects of cognitive function.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Improved neurocognitive function after ECT has been demonstrated by others 15 days (3), 1 month (30), and 3 months (31) after cessation of treatment. At 6 months after ECT, Sackeim et al (2) reported cognitive improvement in most domains assessed, with the notable exception of processing speed, which was still compromised.…”
Section: Discussionmentioning
confidence: 81%
“…Future studies using a longitudinal design having a large number of subjects and psychological and cognitive assessments will be required. Moreover, previous studies showed that cognitive functions were declined immediately after ECT than baseline (Bodnar et al, 2016), but did not change significantly 6 months or 12 months after ECT (Nordanskog, Larsson, Larsson, & Johanson, 2014). Future longitudinal design research with a longer observation period over one year is needed.…”
Section: Discussionmentioning
confidence: 99%